Pelatihan dan Pendampingan Budidaya Sayur Organik di Desa Baros, Kabupaten Serang - Riki Rikardo; Hadi Susilo; Herlina Siti Nurantika (Jurnal Pengabdian Pada Masyarakat, 2017)
TRAINING AND MENTORING OF ORGANIC VEGETABLE CULTIVATION IN BAROS VILLAGE, SERANG REGENCY. The increasing number of people and public awareness about the health of the growing demand for organic vegetables is also increasing. This is one of the business opportunities in the field of organic agriculture, especially organic vegetable cultivation. The economic analysis of organic vegetable cultivation shows that organic vegetable cultivation is profitable, so it can be used as an effort to increase people's income. Organic vegetables are vegetables that are processed by environmentally friendly process, using organic materials from agricultural and livestock waste, without using synthetic chemical fertilizers, and synthetic pesticides. Baros Village, Baros District, Serang District is an agricultural area suitable for organic vegetable cultivation, the availability of land for agriculture, good irrigation, organic fertilizer source widely available, and close to the capital of Banten province. Organic vegetable cultivation uses organic ingredients from agricultural and livestock waste that are around the site. Selection of vegetable seeds is done by selecting seeds that are superior and needed by the community. Soil processing is done by plowing the soil, followed by basic fertilization. Organic vegetable preservation is done with advanced organic fertilization, weeding, irrigation, and vegetable pesticide administration. The harvesting process is done by selecting good organic vegetables, washing, and packing vegetables. The most important aspect of community service programs is the potential for sustainability. The sustainability of the Organic Vegetable Cultivation program is able to support the economy and public health.